Élites económicas vs. candidatos ‘outsiders’ o antiestablecimiento en Colombia : elecciones presidenciales 2018 = Economic elites vs. candidates 'outsiders' or anti-establishment candidates in Colombia: Presidential Elections 2018 (2017)
This article presents the findings of an investigation in which we question the framing that El Tiempo and El Colombiano have given to the presidential candidacies of Sergio Fajardo, Claudia López and Jorge Robledo. The existence of biases in the coverage is evaluated, and the local and national levels are compared in order to evidence the existence of similarities and/or differences. The impact, influence, owners and ideological tendency were the determining factors for the choice of such media. The study uses both an analytical table that accounts for the publications of the chosen media on the candidates to determine the attributed frame, and journalistic standards to analyze such frame (actors, sources and adequacy)